Combinational antidiabetic effects of Curcuma longa L. and Trigonella foenum-graecum L. extracts in alloxan induced type-1 diabetic rats - Shaik, Sadak Basha; Shaik, Sameena Fathima; Shaik, Mannur Ismail; Mhd Sarbon, Norizah; Meesala, Guru Sekhar; Aluru, Sudheer; Pasupuleti, Sreenivasa Rao; Mohammed, Arifullah; Abdul Rahman, Suzanah; Nannepaga, John Sushma; Mohiddin, Syed Siraj; Ramesh, Bellamkonda; et al. (A and V Publication, 2023)
Objective: The current study aimed to determine the combined protective effect of Curcuma longa (CL) and Trigonella foenum-graecum (TFG) on alloxan-induced oxidative stress in liver tissue of albino Wister rats. Methods: Rats were divided into 8 groups with 6 individuals each. Group I served as control, group II, III and IV were treated with CL, TFG and CL + TFG respectively. Group V, VI, VII and VIII were alloxan-induced diabetic rats, whereas group V served as negative control and group VI, VII and VIII were treated with CL, TFG and CL + TFG respectively. Blood glucose, body weight, oxidative enzymes and histopathological changes were evaluated. Results: Group V showed significant increase in blood glucose levels after induction of alloxan, whereas, group VI, VII and VIII showed significantly decreased levels. However, the best hypoglycaemic activity was found in group VIII. The body weights were slightly increased in groups II, III and IV after the treatment of plant extracts, whereas, decreased body weights were noticed in group V. though no significant weight changes were observed in groups VI, VII and VIII. A significant decrease in oxidative enzyme levels as compared to group V were recorded. The histopathological investigation of liver tissue showed morphological alteration in group V and ameliorative effects in group VI, VII and VIII due to administration of CL, TFG and CL + TFG. Conclusion: Therefore, the combined administration of CL + TFG exhibits the highest hypoglycemic activity by reducing the oxidative enzyme levels and regeneration of liver tissue.